Study on Influencing Factors of Paste Coating Thickness of Pervious Concrete - Bobo Xiong; Honghu Gao; Jianguo Chen; Xiaochun Lu; Bin Tian; Bofu Chen; Wanhao Liu (Buildings, 2023)
Pervious concrete (PC) is a multifunctional material with good water permeability, noise reduction, and heat absorption properties. The most critical performance indicators of the PC are permeability and strength, which are mainly affected by the cement paste coating thickness (PCT) on the aggregate surface. The experiment was carried out to study the influence of the water–cement ratio, superplasticizer dosage, aggregate roughness, and aggregate size on PCT, and a new normalization method was proposed for grey correlation analysis to determine the influence degree of the above factors on PCT. Finally, fitting models for predicting the PCT were established based on experimental data. The experimental results indicate that the influence of the water–cement ratio on PCT can be divided into two stages, whereby the PCT shows a slow decline and then a rapid decline with the increase in water–cement ratio; with the increase in superplasticizer dosage, the PCT represents an exponentially decreasing trend; the PCT increases with the aggregate size and aggregate roughness. Based on the grey correlation analysis, the superplasticizer dosage exerts the greatest influence on PCT, followed by the water–cement ratio, aggregate size, and aggregate roughness. The results of this study revealed the change law of PCT under the action of the above factors, which established the premise of controlling the strength and permeability of PC from the perspective of the PCT and provided a reference for the mixture proportion design.